Digital Comic Animation Media Based on THK Improves Conceptual Understanding and Learning Outcomes of Fifth Grade Elementary School Students on the Water Cycle Topic - I Made Ariana Jaya Santika Ariana; I Wayan Widiana; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2025)
Elementary science learning has not optimally developed students’ conceptual understanding and learning outcomes due to limited use of instructional media. This study aims to develop and evaluate the feasibility of a Tri Hita Karana (THK)-based digital comic animation on the water cycle topic. This study employed a development research design using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included material experts, media experts, and elementary school students. Data were collected through non-test and test methods using questionnaires and multiple-choice tests. The data were analyzed using qualitative and quantitative descriptive statistics, as well as inferential analysis through the Paired Sample t-test. The results indicate that the developed media has a very high level of validity based on evaluations from both material and media experts. The practicality level falls into a good category, with positive responses from students during its implementation. Furthermore, the effectiveness test shows a significant improvement in students’ conceptual understanding and learning outcomes after using the developed media. Therefore, the THK-based digital animated comic media is considered valid, practical, and effective for use in learning. The findings imply that the use of innovative, local wisdom-based instructional media can enhance the quality of learning and encourage teachers to develop more creative, contextual, and meaningful learning media.